New Concepts in Bio-diversity Conservation, Publicity and Extension - Environmental Education Centre At Tirumala (Tirupati) - Use of Spiritual Theme - a Case Study - Kumar, S. V.; Raghavaiah, P. S. (Indian Forester, 2000)
Tirumala (Tirupati) is the most popular Hindu temple in the world with an average pilgrim population of 50,000 per day. To spread the message of Bio-diversity Conservation, the Wildlife Wing of Forest Department has setup an Environmental Education Centre, which has a Museum, Library and Audio-visual Room. Spiritual theme is the main plank to impress upon the visitors the inseparable association of man and wildlife since times immemorial and to spread the message that the survival of man depends upon the survival of plant and animal life. Accordingly, most of the displays have this religious theme of Bio-diversity Conservation in which wildlife is worshipped as Gods and Vahanas and Wildlife is associated with Hindu mythology.